Literary for Children: The Values of “Tri Hita Karana” in “Yuyu yang Baik” Story as Children’s Character Education - A.A.S Tantri; G.W Bayu; I.P.M Dewantara (Universitas Pendidikan Ganesha, 2020)
Having good knowledge, skills, and good character is the next generation of superior nation.Many ways can be taken to foster the character of the younger generation, such as through theapplication of the values of “Tri Hita Karana” in the story of the “Yuyu yang Baik” by Cok Sawitri. Thisresearch is a qualitative descriptive study. This study contains the values of “Tri Hita Karana” in“Yuyu's yang Baik” story. Data was collected through data cards and analysed by the Mils andHuberman model. This model goes through three stages, namely: data reduction, data presentation,and drawing conclusions. The conclusion of this study is that character education can be taught toearly childhood based on the values of “Tri Hita Karana” in “Yuyu's yang Baik”.